Kader Kesehatan Menggunakan Pendekatan PAR di Kelurahan Legok - Mila Triana Sari; Miko Eka Putri; Nel Efni; Hesty Hesty; Muhammad Hidayat; Ratu Kusuma; Adetia Havendri; Daryanto Daryanto (Universitas Baiturrahim, 2026)
Pulmonary tuberculosis is a chronic disease that spreads very easily and quickly, posing a national and global health threat. Indonesia ranks second in the world for the highest number of pulmonary TB cases, after India. Low public knowledge, stigma, access to healthcare services, and the long duration of treatment for pulmonary TB are contributing factors to the increase in pulmonary TB cases in Indonesia. The importance of empowering communities and health cadres to prevent transmission and supervise medication intake in pulmonary TB patients aligns with the National Pulmonary TB Elimination Program 2030. This community service aims to increase the knowledge and skills of communities and health cadres in recognizing risk factors, preventing transmission, and supervising treatment for pulmonary TB. The service activity was held on July 17, 2025, and was attended by 22 participants from the community and health cadres. Using a Participatory Action Research (PAR) approach with pre and post tests. Subsequently, education was conducted using interactive face-to-face lectures, discussions, practical demonstrations of effective coughing and cough etiquette, and the distribution of informative leaflets. The follow-up session for the patients' families will be held on July 20, 2025, to conduct direct monitoring at one of the homes of patients with pulmonary TB. The empowerment activities significantly improved the knowledge (p-value 0.004) and behavior (p-value 0.003) of the community and pulmonary TB cadres. The average knowledge score before the activity was 68 (66-74) and increased to 85 (79-91) after the activity. Similarly, the average behavior score increased from 63 (56-74) to 76 (67-87). Health empowerment through education, counseling, and training, as well as the direct use of brochures, proved highly effective in increasing awareness and competence in controlling pulmonary TB. The empowerment activities successfully increased the contribution of health cadres in preventing and early detecting transmission, as well as monitoring the treatment of pulmonary TB patients. There needs to be increased active participation from the community, health cadres, and community leaders so that pulmonary TB elimination can be achieved, especially in the Legok Village.